ANTIMICROBIAL ACTIVITY OF ETHANOLIC EXTRACTS FROM LEAVES OF PISTACIA INTEGERRIMA (ANACARDIACEAE) STEW EX BRAND - VASHIST, HEM RAJ; DOGRA, SHIVANI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Purpose: The ethanol extract of leaves of Pistacia integerrima (EEPI) was evaluated for antibacterial activity. Methods: The leaves of P. integerrima were collected from wild source and authenticated by Dr. Manoj Joshi, botanist environmental education expert, Una, HP, India. Antimicrobial activity was performed using the Mueller–Hinton (MH) agar using disk diffusion method. In the MH agar media 38 g after dissolving in 1000 ml of distilled water (pH 7.3±0.2), the extract was incorporated such that concentration per ml will be 66.67 μg, 133.33 and, 166.66. Results: The minimum inhibitory concentration recorded was 133.33 for Pseudomonas aeruginosa, Salmonella Typhi, and Klebsiella pneumonia, whereas 166.6 for Staphylococcus aureus, Coagulase-negative Staphylococcus, and Escherichia coli. The maximum zone of inhibition was found 19 mm and 18 mm for S. aureus and E. coli, respectively. S. aureus have been reported for skin pneumonia, heart valve, and bone infections whereas E. coli causes diarrhea and many other infections in children. Conclusion: After reporting the better zone of inhibition for these two bacteria, EEPI can be used to formulate better herbal remedy against them.